Pengembangan Peran Posyandu melalui Pendidikan Gizi pada Ibu Balita dan Kader - Luluk Ria Rakhma; Nur Lathifah Mardiyati (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Posyandu is a health institution that has direct contact with the community, therefore the posyandu located in the middle of community unit is the front line of health services. Cadres as health workers at the village level should be equipped with knowledge, skills and tools to support mothers of children under five so that they can carry out cadre duties well. In addition to the role of a posyandu cadre, the role of the family is also important in overcoming nutritional problems such as stunting, but there is still minimal knowledge related to nutrition for posyandu cadres and mothers of toddlers. Therefore, activities are needed to increase the knowledge and skills of posyandu cadres and mothers of children under five. This service activity was carried out in Cabeyan Village, Bendosari, Sukoharjo in 2020 with partners for mothers of toddlers and Posyandu Tamansari and Puspitasari cadres. Cabeyan Village has the highest number of children under five with short nutritional status among 14 villages in Bendosari District, Sukoharjo by 9%. The service activities carried out were: 1) Training on measuring nutritional status using the anthropometric method for posyandu cadres, 2) Demonstration of making Supplementary Food for Posyandu cadres and 3) Nutrition consultation regarding Infant Toddler Feeding for mothers of toddlers. The result of this activity is that there is an increase in knowledge and skills of posyandu cadres related to measuring nutritional status and making additional food as well as knowledge of mothers under five regarding infant and child feeding.